IMPLEMENTASI PEMBERIAN REHABILITASI TERHADAP PECANDU NARKOTIKA DI BNN KOTA DENPASAR - Rusdiawan, Sang Putu Aditya; Saraswati, Putu Sekarwangi (Jurnal Hukum Mahasiswa, 2024)
The State of Indonesia is a state of law, this can be seen from article 1paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that "The State of Indonesia is a state of law. Where the state of law is defined simply is a state whose administration of government power is based on law. Along with the times, someone at first lay with narcotics turned into an addict who was difficult to escape his dependence, drug addicts suffered from dependency syndrome as a result of self-inflicted drug abuse. Rehabilitation of drug addicts is a treatment process to free drug addicts is a form of social protection that integrates drug addicts into social order so that he no longer abuses drugs. Based on the law, there are at least two types of rehabilitation, namely medical rehabilitation and social rehabilitation The main problem that will be examined is how the implementation of the law on providing rehabilitation for drug users by BNN Denpasar City then what are the factors that hinder BNN in providing rehabilitation for drug users in Denpasar City. Judging from its type, this research is a sociological research, namely by conducting a survey by going directly to the field that is pleased with the problem to be studied, namely at BNN Denpasar City Based on the results of the author's research, the services provided by BNN Denpasar City are still not optimal for drug abuse and addicts. Due to limited funds provided by the government for BNN Denpasar City. But even though the funds provided by the government have been decided to carry out rehab in hospitals, BNN Denpasar City can still provide rehabilitation services by providing an examination, diagnosis, treatment and treatment and treatment for drug abuse and addicts. The obstacle faced is the uncooperation of patients with BNN Denpasar City by reusing narcotics and lying while in rehab. Here the role of family is also important in the rehab process.